The influence of micropores on the dynamic–mechanical properties on reinforced epoxy foams - Bledzki, A. K; Kurek, K; Gassan, J (Journal of materials science, 1998)
The subject of this investigation is the influence of the content of micropores on the mechanical properties of fibre-reinforced epoxy foams. The reinforcement was made of glass or carbon fabrics. A foam-like composite was achieved, which contained 42.0 vol% glass fibres, 27.4 vol% micropores at a density of 1.4 g cm-3. When the foam was reinforced with 50 vol% carbon fibres the composite contained 15 vol% micropores.The load increasing test for these reinforced foams showed an interdependence between the damping and the content of micropores; the breaking stress decreased with increasing micropore content.The Wohler fatigue test showed similar curves, the fatigue limit decreased with increasing micropore content.The most distinct influence of micropores on the composite was observed at the impact test. The loss energy increased with increasing content of micropores. © 1998 Kluwer Academic Publishers